Characterization of Pd/TiO2/Si metal-insulator-semiconductor sensors for hydrogen detection - Shubham K.; Khan R.U.; Chakrabarti P. (My University, 2025)
In the present paper, the capacitance versus gate voltage (C-V) response of Pd/TiO2/Si MIS capacitor as a function of hydrogen gas concentration at 200 kHz frequency has been reported. Pd/TiO2/Si MIS capacitor was studied for gas sensing capability in respect of hydrogen with concentration varying from 0.1 ppm to 2 ppm at different operating temperatures (room temperature to 150 °C). The response of the sensor was measured as a shift in C-V curve of the MIS capacitor. The sensing signal originates from the variation in flat-band voltage which increases with an increase in hydrogen gas concentration. High sensitivity of the sensor is attributed to the large change of interface state charges because of the large surface to volume ratio of the nano-structured TiO2. The values of response time as well as the recovery time have also been estimated and are found to be comparable to that observed in the case of conventional MOS structure. © 2013 American Scientific Publishers.